Constructing vesicle-based artificial cells with embedded living cells as organelle-like modules - Elani,Y; Trantidou,T; Wylie,D; Dekker,L; Polizzi,K; Law,R; Ces,O (Scientific Reports, 2018)
There is increasing interest in constructing artificial cells by functionalising lipid vesicles with biological and synthetic machinery. Due to their reduced complexity and lack of evolved biochemical pathways, the capabilities of artificial cells are limited in comparison to their biological counterparts. We show that encapsulating living cells in vesicles provides a means for artificial cells to leverage cellular biochemistry, with the encapsulated cells serving organelle-like functions as living modules inside a larger synthetic cell assembly. Using microfluidic technologies to construct such hybrid cellular bionic systems, we demonstrate that the vesicle host and the encapsulated cell operate in concert. The external architecture of the vesicle shields the cell from toxic surroundings, while the cell acts as a bioreactor module that processes encapsulated feedstock which is further processed by a synthetic enzymatic metabolism co-encapsulated in the vesicle.